Electromagnetic Waves and Material Properties - Yıldırım, Osman; Balta, Torehan (My University, 2009)
The standard impedance condition is the simplest way of simulating the material properties of a planar surface. This method is only accurate if the coating is very thin or lossy. To improve the accuracy, generalized impedance conditions can be used to simulate the material properties of a planar surface. The accurate solution of a scattering problem via planar slab depends on its thickness, the wavelength of incident wave, and material properties of the slab. Since boundary condition is local in character, accuracy decreases when the slab is illuminated at near grazing angle. Accuracy also decreases if the slab has a curved shape. To increase accuracy or provide a better simulation of the material, we have to search for alternative conditions. In this study, the Taylor series method is applied to a planar slab. This method gives reasonable solution even if slab has a curved shape. Power reflection and transmission coefficients are depicted versus different impedance and observation angles.
Keywords: Boundary Conditions; Material Properties; Reflection; Transmission